cuentas por pagar del Minimarket “Xavier Rueda” de la ciudad de Babahoyo, durante los periodos 2022 - 2023. - Moran Monar, Luis Alexander (2025)
The study analyzes the management of accounts payable at the Xavier Rueda 24/7 Mini Market in Babahoyo during 2022-2023. It was identified that the company faces control problems in its accounts payable, which affects its liquidity and financial stability. The lack of planning and monitoring has generated delays in payments and accounting errors. This can lead to sanctions, loss of discounts and impact on business relationships. The company does not carry out regular technical evaluations on its liabilities, which makes financial decision-making difficult. Tools such as the current liquidity ratio, acid test and horizontal analysis were applied to evaluate the financial situation. The results show that the company has a high level of debt and insufficient liquidity. The variation in accounts payable increased by 231.97%, affecting the stability of the business. It is recommended to implement internal controls, optimize cash flows and establish strategies to reduce the financial burden. The debt ratio is 0.9286, higher than the recommended margin, indicating high risk. It is advisable to make prudent decisions about debt and improve financial planning. A detailed analysis of liabilities is crucial to avoid inconsistencies and liquidity problems. The lack of internal controls compromises the viability of the company. It is proposed to improve payment management to guarantee solvency. Resolving these issues will allow you to maintain stable operations and healthy business relationships. The company must implement strategies to improve its payment capacity and reduce financial risks.